Time‐Lapse Imaging of Glial–Axonal Interactions. Issue 1 (1st July 2015) - Ioannidou, Kalliopi; Edgar, Julia M.; Barnett, Susan C.
Abstract: In the central nervous system (CNS), myelin is formed by oligodendrocytes that are derived from precursor cells, known as oligodendrocyte precursor cells (OPCs). Successive stages of OPC interactions with the axons can be visualized in vitro and ex vivo using mixed neural cell cultures and pieces of intact spinal cord, respectively. OPCs and their differentiation can be imaged using cell‐type‐specific markers or green fluorescent protein (GFP) tags. This protocol describes methodology for generating these two systems for time‐lapse imaging of dynamic cell interactions using fluorescent and 2‐photon microscopy. © 2015 by John Wiley & Sons, Inc.